The Impact of SARS-CoV-2 Outbreak on Primary Sjögren's Syndrome: An Italian Experience - Carubbi, Francesco; Alunno, Alessia; Ferri, Claudio; Gerli, Roberto; Bartoloni, Elena (Frontiers in Medicine, 2020)
Objective: Since no data is available about the personal experience of people with primary Sjögren’s syndrome (pSS) with regard to disease burden and management during the novel Severe Acute Respiratory Syndrome coronavirus (SARS-CoV)-2 outbreak, we aimed to explore these aspects with the ultimate goal to identify unmet needs and priorities. Methods: A telephone consultation was scheduled with patients with pSS and information regarding the disease status, ongoing treatment and symptoms/diagnosis of coronavirus disease 2019 (COVID-19) were collected. Clinical records were retrospectively evaluated to gather pre-COVID-19 information. Results: 102 patients with pSS were contacted. Most rheumatology consultations and other pSS-related tests were cancelled during the SARS-CoV-2 outbreak. Less than 30% of patients contacted the rheumatologist via telemedicine despite experiencing disease flares or therapy shortage. Disease activity and patient reported symptoms significantly worsened during the closure period. All patients practiced social distancing, most of those employed switched to smart working and different work settings impacted on the type of symptom worsening. Conclusion: This is the first study addressing the personal experience of pSS patients resulting from the impact of the SARS-CoV2 outbreak and it identifies unmet needs and priorities requiring to be addressed. Our findings may help designing individualized strategies